PENGARUH LAYANAN BIMBINGAN KONSELING TERHADAP PENURUNAN KENAKALAN SISWA - Kulsum, Umi; Aziz, Azizah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
Guidance and counseling services are aimed at helping to overcome many difficulties faced by girls both personal problems, learning, social and career. To overcome forms of student delinquency needed efforts of schools, especially teacher guidance and counseling to both prevention and cure. Research on the effects of guidance and counseling services on the decline in delinquency Schoolgirl MTs. Al Falah Ampel Wuluhan Jember with respondents who researched many as 20 students from class VII is taken as a whole. Based on the results of the study, the statistical results obtained were 0.241 in the range 0.20-0.40 which means that juvenile delinquency in MTs. Al Falah falls into the low category. Thus there is the influence of guidance and counseling services to the decline of student misbehavior in MTs. One-Stop Al Falah Wuluhan Jember and low influence. Keywords : Guidance and counseling services, decreased student delinquency